1925 Or. Gen. and Special Laws 42, ch. 31, §§ 1-2 - (:unkn) unknown (My University, 1925)
Prohibited the setting of any loaded spring gun. Punishable by a fine of $100-500 or imprisonment for 30 days to 6 months. Exception for setting of trap gun to destroy burrowing rodents.
Keywords: TRAP GUNS